Pengaruh Pembelajaran Daring Dengan Media Video Terhadap Keterampilan Mengajar Mahasiswa PPLK 2 Fakultas Keguruan Dan Ilmu Pendidikan Universitas Banten Jaya - Nely Hartika; uswatun hasanah (-)
This research aims to find out the influence of online learning with video media on the teaching skills of PPLK  2 students. This research was conducted at the faculty of teacher training and education at banten jaya university. The population in this study is all students of the faculty of teacher training and education of bantenuniversity,  who  have  carried out the practice of online education field experience with a total of 67 students, sampling techniques from this study using saturated sampling.  Data collection techniques use questionnaires, documentation, library studies. In this study first conducted instrument testing, namely by conducting a test of validity and reliability, then conducting a data normality test, simple linear regression, hypothesis test (T Test) and the last test of determination coefficient test using SPSS 26. Based on the results of the T Test (hypothesis) obtained acalculated t value of 10.679 while ttable  1.99714.  This indicates that tcalculates  > ttable  or 10.679>1.99714, so H0 is rejected and Ha  is accepted. Then there is the influence of online learning with video media on the teaching skills of PPLK 2 students.